Creation of fiber art from fabric waste using weaving, collage, and patchwork techniques - Wahida, Adam; Murni, Endri Sintiana (International Journal of Visual and Performing Arts, 2025)
In addition to contributing to economic growth, the textile industry has the potential to produce large amounts of fabric waste, which often ends up in trash cans and pollutes the environment. Responding to these conditions, this study aims to explore the use of fabric waste as the main material in the creation of fiber art, evaluate environmental and economic benefits, and see positive impacts on society. This research uses an art practice-based approach to create fiber art from waste materials using weaving, collage, and patchwork techniques. The method includes collecting and selecting fabric waste based on the type of textile material, applying various artistic techniques, and analyzing the aesthetics and functionality of the artwork made. The results of the study show that textile waste created through a combination of weaving, collage, and patchwork techniques can produce artistic and aesthetic fiber artworks.Â  This fiber artwork contributes to the concept of sustainability in fine art and emphasizes that fabric waste can be converted into creative products to extend the life cycle of materials. Thus, it can open new opportunities in the recycling-based creative industry.